Two new species of Xanthagaricus and some notes on Heinemannomyces from Asia - Md. Iqbal Hosen; Zong-ping Song; Genevieve Gates; Samantha C. Karunarathna; M. Salahuddin M. Chowdhury; Tai-Hui Li (MycoKeys, 2017)
Xanthagaricus flavosquamosus and X. necopinatus, two new species of Agaricaceae, are described and illustrated from Asia. Macroscopically, both species are closely related to each other, but there are obvious micromorphological and molecular differences between them. Morphological and phylogenetic data showed that the two new species are distinct from other known species of the genus Xanthagaricus. Xanthagaricus flavosquamosus from China is characterized by its small, yellow basidiomata, short clavate cheilocystidia, epithelial pileipellis, and verrucose basidiospores measuring 5–5.5 × 3–3.5 μm. Xanthagaricus necopinatus from Bangladesh is characterized by having small, yellow basidiomata, a fugacious annulus, clavate to narrowly clavate cheilocystidia, epithelial pileipellis, and rugulose-rough basidiospores measuring 4–5 × 2.7–3.2 μm. In addition to the new species, a Heinemannomyces collection from China is reported. Morphological data and molecular phylogenetic analyses fully support the Chinese collection being Heinemannomyces splendidissimus, a species of Agaricaceae, originally described from Southeast Asia. Detailed descriptions, color photos and illustrations of the three species are presented. A key to the genus Xanthagaricus occurring in Bangladesh and China is provided.